Flexible manufacturing systems recent developments - Raouf, A. 1929- (Abdul).; Ben-Daya, M. (Mohamed).; International Conference on Production Research Windsor, Ont.) 1983 (Amsterdam Elsevier, 1995)
"This volume contains new and updated material from Flexible manufacturing: recent developments in FMS, robotics, CAD/CAM, CIM which was a selection of papers presented at the VIIth International Conference on Production Research, held in Windsor, Ontario during 1983"--Pref.
Keywords: Flexible manufacturing systems